Multi-omics elucidation of Lactiplantibacillus plantarum NKK20 in preventing PCOS via the gut-ovary axis: SCFAs-mediated microbiota-metabolite-immune crosstalk - Xu, Hao; Liu, Xinyu; Sun, Wen; Dong, Xueyun; Liu, Xuehui; Xie, Yunhan; He, Jiayuan; Ali, Asmaa; Chen, Min; Wu, Liang; Ma, Jie; Shao, Keke (Frontiers in Nutrition, 2026)
PurposePolycystic ovary syndrome (PCOS) is a clinically prevalent endocrine and metabolic disorder characterized by gut microbial disturbances and chronic low-grade inflammatory responses.MethodsThis study explores the therapeutic potential and mechanistic insights of Lactiplantibacillus plantarum NKK20 (LP) in a PCOS murine model established through high-fat diet (HFD) and letrozole co-induction. By integrating multi-omics profiling (16S rRNA sequencing and untargeted metabolomics) with histopathological evaluation, we systematically assessed LP-mediated modulations of gut microbiota composition, metabolic signatures, ovarian function, and intestinal barrier integrity.ResultsThe results demonstrated that LP administration effectively counteracted metabolic dysregulation in PCOS mice, mitigating body weight gain, ameliorating lipid abnormalities (reduced total cholesterol, triglycerides, and LDL-C alongside elevated HDL-C), and lowering fasting glucose levels. Hormonally, LP suppressed hyperandrogenism, as evidenced by decreased testosterone, while rebalancing inflammatory mediators through IL-10 upregulation and concomitant reduction of TNF-α, IL-6, IL-1β, and MCP-1. Ovarian histomorphology revealed attenuated follicular cysts and enhanced luteinization. Critically, LP restored intestinal homeostasis by (i) augmenting short-chain fatty acid (SCFA) production—particularly butyrate—(ii) fortifying the gut barrier via increased ZO-1 and occludin expression, and (iii) diminishing circulating endotoxin. Microbial sequencing identified enrichment of Bacteroidetes and Muribaculum following LP treatment. Serum metabolomics further uncovered LP-induced normalization of steroid hormone biosynthesis and glycerophospholipid metabolism, coinciding with elevated anti-inflammatory mediators such as 6a-prostaglandin I1.ConclusionCollectively, these findings delineate a novel preventive axis through which LP inhibits PCOS progression — namely, via coordinated “gut microbiota–metabolite–ovarian” crosstalk involving SCFA-mediated barrier restoration, microbial ecology stabilization, and suppression of ovarian inflammatory onset. This work advances the translational rationale for probiotic-based strategies in PCOS prevention.